AgriTech4Kenya innovation challenge 2024-2025: Accelerator Program and Demo Day Report - Bhansali, Malvika; Khader, Taija; Wafullah, Teresah N. (2025)
The AgriTech4Kenya Innovation Challenge is a groundbreaking initiative powered by the CGIAR Accelerate for Impact Platform of the Alliance of Bioversity International and CIAT. The effort is co-organized with the CGIAR Excellence in Agronomy Initiative and CGIAR Initiative on Nature-Positive Solutions. Funded by the Italian Ministry of Foreign Affairs and International Cooperation, the project is implemented in partnership with Micro Enterprise Support Programme Trust, Kenya National Innovation Agency, AGRA, Agricultural Sector Network Daystar University, iTATU, Mercy Corps, DOB Equity, Climate Resilient Africa Fund, Sustainable Agriculture Foundation Africa (SAF-Africa) and Kenya Agricultural Livestock and Research Organization. The Pangea Accelerator supported the project. The challenge aims to advance innovative solutions to address critical challenges within Kenya’s agricultural sector. Read more on the Accelerator Program and Demo Day Report.